2009
DOI: 10.2353/ajpath.2009.090544
|View full text |Cite
|
Sign up to set email alerts
|

Unique Lipids from a Common Human Bacterium Represent a New Class of Toll-Like Receptor 2 Ligands Capable of Enhancing Autoimmunity

Abstract: Recent reports suggest that commensal bacteria may play a down-regulatory role in autoimmune disease. In the present studies, we demonstrate that phosphorylated dihydroceramides, uniquely structured lipids derived from the common human oral bacterium Porphyromonas gingivalis and from bacteria commonly found in the gastrointestinal tract and other organs, are capable of enhancing autoimmunity. We have previously reported that these lipids have proinflammatory effects on human fibroblasts in vitro and, in prelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
72
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 31 publications
1
72
0
Order By: Relevance
“…In addition to P. gingivalis proteins and LPS penetrating gingival tissue, P. gingivalis phosphorylated dihydoceramide lipids have been isolated from gingival tissue and subgingival plaque of chronic periodontitis patients (52)(53)(54). Whole P. gingivalis cells and certain components, including the RgpA-Kgp complexes and lipids, induce secretion of a number of proinflammatory cytokines from epithelial and fibroblast cells in vitro, such as IL-1, IL-6, IL-8, PGE 2 , macrophage chemoattractant protein (MCP)-1a, and ICAM-1 (50,54,55).…”
mentioning
confidence: 99%
“…In addition to P. gingivalis proteins and LPS penetrating gingival tissue, P. gingivalis phosphorylated dihydoceramide lipids have been isolated from gingival tissue and subgingival plaque of chronic periodontitis patients (52)(53)(54). Whole P. gingivalis cells and certain components, including the RgpA-Kgp complexes and lipids, induce secretion of a number of proinflammatory cytokines from epithelial and fibroblast cells in vitro, such as IL-1, IL-6, IL-8, PGE 2 , macrophage chemoattractant protein (MCP)-1a, and ICAM-1 (50,54,55).…”
mentioning
confidence: 99%
“…Our previous studies indicated that hydrolysis of plaque or gingival tissue lipid extracts yields substantial levels of 3-OH iso C 17:0 , which could reflect the presence of bacterial lipids, including dihydroceramide lipids or free lipid A species. We now conclude that 3-OH iso C 17:0 previously recovered from lipid extracts of diseased dental samples (26,29) does not reflect the presence of phosphorylated lipid A of P. gingivalis.…”
Section: Resultsmentioning
confidence: 60%
“…In summary, the levels of monophosphorylated lipid A species in all dental samples from periodontitis disease sites were negligible compared with the phosphorylated dihydroceramide lipids. Therefore, the previously reported recovery of 3-OH iso C 17:0 in lipid extracts of diseased teeth and subgingival plaque (26,29) does not result from the presence of free lipid A species. The Tri-Reagent method was previously shown to extract LPS constituents from P. gingivalis that contain diphosphorylated penta-acylated lipid A species as well as monophosphorylated tetra-and penta-acylated lipid A species, whereas the MgCl 2 /…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations